1H NMR study and multivariate data analysis of reindeer skin tanning methods. (17th October 2016) - Zhu, Lizheng; Ilott, Andrew J.; Del Federico, Eleonora; Kehlet, Cindie; Klokkernes, Torunn; Jerschow, Alexej
Abstract : Reindeer skin clothing has been an essential component in the lives of indigenous people of the arctic and sub‐arctic regions, keeping them warm during harsh winters. However, the skin processing technology, which often conveys the history and tradition of the indigenous group, has not been well documented. In this study, NMR spectra and relaxation behaviors of reindeer skin samples treated with a variety of vegetable tannin extracts, oils and fatty substances are studied and compared. With the assistance of principal component analysis (PCA), one can recognize patterns and identify groupings of differently treated samples. These methods could be important aids in efforts to conserve museum leather artifacts with unknown treatment methods and in the analysis of reindeer skin tanning processes. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Principal component analysis of spectral and relaxation NMR data from differently treated reindeer skin samples produces groupings according to the skin treatment methods. The results give insights into the underlying chemical processes involved and can aid in the conservation of museum leather artifacts, where knowledge of the original skin preservation methods is important.